2022
DOI: 10.3390/polym14183738
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Nanocomposite Based on Edible Gelatin Film as Active Packaging from Clarias gariepinus Fish Skin with the Addition of Cellulose Nanocrystalline and Nanopropolis

Abstract: This study develops bio-nano composite gelatin-based edible film (NEF) by combining nanogelatin, cellulose nanocrystal (CNC), and nanopropolis (NP) fillers to improve the resulting film characteristics. The NEF was characterized in terms of thickness, swelling, pH, water content, solubility, vapor and oxygen permeability, mechanical properties, heat resistance, morphology, transparency, and color. The results showed that the thickness and swelling increased significantly, whilst the pH did not significantly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…The addition of other macromolecules such as polysaccharides, film preparation method, and drying process are factors influencing the thickness of gelatin-based films. Our results are in agreement with other studies (Hoque et al, 2010;Govindaswamy et al, 2018;Lupina et al, 2022;Ratna Aprilia et al, 2022). They found that a low increase in the thickness is usually due to the protruding construction formed during film formation by gelatin strands.…”
Section: Physical Properties (Solubility Moisture Contact Angle Film ...supporting
confidence: 94%
See 1 more Smart Citation
“…The addition of other macromolecules such as polysaccharides, film preparation method, and drying process are factors influencing the thickness of gelatin-based films. Our results are in agreement with other studies (Hoque et al, 2010;Govindaswamy et al, 2018;Lupina et al, 2022;Ratna Aprilia et al, 2022). They found that a low increase in the thickness is usually due to the protruding construction formed during film formation by gelatin strands.…”
Section: Physical Properties (Solubility Moisture Contact Angle Film ...supporting
confidence: 94%
“…In complexes, there are electrostatic interactions that present enhanced thermal stability. Previous studies showed that gelatin‐based film formulations containing natural phenolic compounds can form a strong gelatin network with the phenolic molecules, able to raise the denaturation temperature and increasing the thermal durability of the films (Ratna Aprilia et al, 2022; Wang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These observed differences between the formed biocomposites blend films may be explained by the free volume theory of the glycerol effect, which increases the intermolecular spaces between the film chains, thus resulting in increased film thickness [ 40 , 48 ], as well as the increase in the solid content in the films containing GA and XG, which have the highest thickness values (0.124 and 0.105 mm, respectively). In fact, Ratna et al [ 15 , 50 ] stated that biocomposite edible film thickness can be increased by adding solid materials to composite film. Similarly, Kaya et al [ 51 ] observed that the inclusion of vegetable extract in chitosan-based film increased film thickness from 45.4 μm (control) to 99.2 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their hydrophilicity, gelatin films have disadvantages such as high water solubility and low water vapor barrier properties (Nilsuwan, Guerrero, et al., 2019). Bio‐nanocomposite gelatin‐based edible film from dumbo catfish skin was prepared by combining nanogelatin, cellulose nanocrystal, and nanopropolis fillers, which significantly improved the properties of the resulting film characteristics (Ratna et al., 2022).…”
Section: Biopolymers From Sfbpmentioning
confidence: 99%